2006
DOI: 10.1055/s-2006-951743
|View full text |Cite
|
Sign up to set email alerts
|

Glukosemessung mit dem kontinuierlich messenden Glukosesensor CGMS® bei stoffwechselgesunden Schwangeren während Betamethasontherapie zur fetalen Lungenreifeinduktion

Abstract: Pregnant patients have high glucose measurements for two days during betamethasone therapy. No maternal acidosis and no diabetic delayed metabolic effects were seen, and fetal outcome showed good results. A prophylactic use of insulin is not generally needed in healthy women.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…However, there are no guidelines for cases like this without diabetes mellitus. Star et al reported that prophylactic use of insulin was better [7], but Schumacher et al opposed this notion [8]. It is very difficult to extrapolate from these overseas reports why substantial tocolytic therapy in Japan is different from that in those other countries.…”
Section: Introductionmentioning
confidence: 99%
“…However, there are no guidelines for cases like this without diabetes mellitus. Star et al reported that prophylactic use of insulin was better [7], but Schumacher et al opposed this notion [8]. It is very difficult to extrapolate from these overseas reports why substantial tocolytic therapy in Japan is different from that in those other countries.…”
Section: Introductionmentioning
confidence: 99%